Prenatal incarceration exposure and adverse COVID-19 related experiences during pregnancy - Fahmy, Chantal (Journal of crime and justice, 2025)
This study examines the relationship between exposure to incarceration and stressful experiences endured during the initial months of the COVID-19 pandemic (June-December 2020). Using data from the 2020 Pregnancy Risk Assessment Monitoring System (PRAMS), multiple Poisson and logistic regression models were used to assess the association between incarceration of a woman or her partner in the year before birth and the likelihood of experiencing 13 different types of adverse experiences due to the COVID-19 pandemic between June and December 2020. Results indicate that women’s incarceration exposure – either personally or vicariously through a partner – was associated with more total COVID-19 experiences. Additionally, women with incarceration exposure encountered several adverse experiences, including problems paying rent, mortgage, or bills, worried food would run out, felt more anxious, felt more depressed, had more verbal augments or conflicts with husband/partner, and husband/partner was more physically, sexually, or emotionally aggressive, than their non-incarceration-exposed counterparts. Implications of the findings for theory and public policy are discussed.